Quantitative easing in a small open economy: An international portfolio balancing approach - Serdar Kabaca (Bank of Canada, 2016)
This paper studies the effects of quantitative easing (QE) in a small open economy dynamic stochastic general-equilibrium model with international portfolio balancing. Portfolios are classified as imperfectly substitutable short-term and long-term subportfolios, each including domestic and foreign bonds. Unlike in standard small open economy models, both domestic and foreign bonds may be traded internationally. The model links the domestic term premium to the global term premium, and the implication of the model on the effectiveness of QE policies in reducing the domestic term premium depends crucially on the degree of substitutability between domestic and foreign bonds. The estimated model implies that QE in small open economies is expected to be much less effective on long-term yields because of the high substitutability between home and foreign assets found in the data. In the model, this causes the effect on the exchange rate to be limited. The paper also shows that foreign investors' access to the domestic debt market is essential when evaluating the QE policy; ignoring foreign investors' access would mistakenly make the policy look more effective.
Keywords: E52; F41; 330; Transmission of monetary policy; International topics